Effect of inadequate ferrule segment location on fracture resistance of endodontically treated teeth - Satheesh B Haralur; Ahmed Fatis Alalyani; Mohammad Ali Almutiq; Abdulrahman Ahmed Alfaifi; Amer Abdullah Al-Shehri (Wolters Kluwer Medknow Publications, 2018)
Introduction: The circumferential 2 mm ferrule during the fabrication of the crown is strongly advocated for the long-term clinical success. During the routine clinical practice, the dentist encounters the endodontically treated tooth (ETT) with inadequacy of the ferrule in some segment due to caries, abrasion, and erosions. The aim of this in vitro study was to investigate the consequence of inadequate segmental ferrule location on fracture strength of the root canal-treated anterior and posterior teeth. Materials and Methods: Fifty each maxillary canine and mandibular premolar intact human teeth were root canal treated and sectioned at 2 mm above the cementum-enamel junction. The teeth samples were divided into 5 groups of 10 each. The G-I and G-V samples had the 360° ferrule and complete absence of the ferrule, respectively. The G-II had the inadequate ferrule on the palatal surface, while G-III and G-IV had inadequate ferrule at buccal and proximal area. Teeth samples were subsequently restored with glass-reinforced fiber post, composite core, and full veneer metal crown. The samples were tested with universal testing machine under static load to record the fracture resistance. The acquired data were subjected to ANOVA and Tukey's post hoc statistical analysis. Results: The G-I with circumferential ferrule showed the higher fracture resistance. The teeth samples with lack of the ferrule had the least fracture resistance. Among the segmental absence of ferrule, teeth samples with lack of the proximal ferrule were least affected. Deficiency of a ferrule on the lingual wall significantly affected the fracture strength in both anterior and posterior ETT. Conclusions: The ETT with sectional inadequacy of the ferrule is significantly more effective in resisting the fracture in comparison to the complete absence of the ferrule.